2011
DOI: 10.1186/1476-072x-10-5
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular disease occurrence in two close but different social environments

Abstract: BackgroundCardiovascular diseases estimate to be the leading cause of death and loss of disability-adjusted life years globally. Conventional risk factors for cardiovascular diseases only partly account for the social gradient. The purpose of this study was to compare the occurrence of the most frequent cardiovascular diseases and cardiovascular mortality in two close cities, the Twin cities.MethodsWe focused on the total population in two neighbour and equally sized cities with a population of around 135 000 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
33
0
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 40 publications
5
33
0
1
Order By: Relevance
“…Regarding the type of occupation, it has been associated with CVD development, with blue-collar workers or low-level employees having increased mortality [32,33], as well as higher likelihood for a coronary [34,35] or a stroke event [36]. As far as blue-collar workers are concerned, they generally have to cope with higher occupational stress and may turn to unhealthier behaviors, such as smoking, as a means for anxiety reduction [37].…”
Section: Discussionmentioning
confidence: 98%
“…Regarding the type of occupation, it has been associated with CVD development, with blue-collar workers or low-level employees having increased mortality [32,33], as well as higher likelihood for a coronary [34,35] or a stroke event [36]. As far as blue-collar workers are concerned, they generally have to cope with higher occupational stress and may turn to unhealthier behaviors, such as smoking, as a means for anxiety reduction [37].…”
Section: Discussionmentioning
confidence: 98%
“…Figure 2D demonstrates characteristic resonances of NHCH 2 CH 2 protons in PEI at 2.4 ppm to 3.2 ppm. 3,29 The content of LA and MMD was almost same in P(MMD-co-LA) blocks of mPEG-b-P(MMDco-LA) and star-shaped P(MMD-co-LA)-OH calculated according to 1 H NMR. These results suggested that mPEGb-P(MMD-co-LA) and cationic P(MMD-co-LA)-g-PEI copolymers were synthesized successfully.…”
Section: Synthesis Of Copolymermentioning
confidence: 99%
“…1 Coronary bypass surgery is one of the most vital procedures for treating occluded coronary arteries. 2,3 However, restenosis of artificial blood vessels usually leads to the failure of the surgery.…”
Section: Introductionmentioning
confidence: 99%
“…The inhabitants of the blue collar city are generally less educated, are more often smokers, exercise less, are more overweight, have more periods of sick leave, have shorter life expectancy and a higher frequency of cardiovascular disease, gastrointestinal disorders, but also mental illness, musculoskeletal disease, and rheumatism, etc. These differences seem to have remained stable over the years (Wennerholm et al 2011, Grodzinsky et al 2012.…”
Section: Samplesmentioning
confidence: 82%
“…Social factors such as low socioeconomic status, including a poor residential area, low educational level, a low-status job, and low income predispose for CVD (Perk et al 2012), especially in working ages (Reinier K, 2011). A higher presence of classical risk factors in low socioeconomic groups only partly explains the difference (Wennerholm et al 2011).…”
Section: Health Inequalities and Cardiovascular Disease (Cvd)mentioning
confidence: 99%